Perfil nutricional de crianças expostas ao HIV acompanhadas no estado do Tocantins - Gratão, Lucia Helena Almeida (Universidade Federal do Tocantins, 2018)
HIV infection compromises the immune system causing destruction of the cells mostly hosted as LT-CD4+. The virus can be transmitted through sexual intercourse, blood transfusion, contact with contaminated puncture materials, vertical transmission and breastfeeding. As a prophylactic measure for a vertical transmission the use of highly active antiretroviral therapy (HAART) is adopted from the fourteenth week of gestation, which advocates a reduction of the viral load to undetectable levels until the moment of delivery. However, there are no problems that can cause HAART, which can not be created in life in training and in the neonatal period, as well as the effect of this treatment on infant growth and development. Initially, a literature search was carried out in a systematized manner in the National Library of Medicine (National Institutes of Health (PubMed), Virtual Health Library (VHL) databases that includes the Medical Literature Analysis and Recovery System Online (MEDLINE ), Latin American and Caribbean Literature in Health Sciences (LILACS), Nursing Database (BDENF) and SciELO (Scientific Electronic Library Online). (1) "HIV HIV Brazil", (2) "HIV adolescent HIV", (3) "HIV anthropometry Brazil" and (4) "HIV Brazil nutritional assessment", adding "e" filter For advanced research. Thirteen articles were selected after reading in their entirety. These studies contributed to the development of a retrospective cohort study of 140 uninfected exposed children attended at a referral service specializing in the care of people living with HIV / AIDS in Palmas, Tocantins, Brazil. Data were collected from children at birth and subsequent visits categorized in three moments (m0, m1, m2 and m3) and maternal information. Anthropometric indexes (weight-for-age, weight-for-height, body-for-age-for-age, weight-for-height and cephalic-for-age) were used to verify nutritional status and proportionality indices cephalic by thoracic perimeter, Roher index and head circumference weight). The statistical tests of X², t-student, Tukey, Friedman and ANOVA and Kruskall Wallis were used. They show that regardless of whether it is HIV activity in the host or by the use of HAART, children living with HIV / AIDS may present changes in bone metabolism, but adequate intake and serum micronutrient monitoring may prevent such disorders. There is also association of HAART with dyslipidemia and lipodystrophy in the populations studied. The cohort study showed a tendency to risk of overweight or overweight during follow-up, as well as statistical significance in relation to the early introduction of food and the values of CD4 and CD8. No changes were found in the proportionality indices. The shortage of research with Brazilians made the correlations more difficult. It is concluded that the monitoring of the nutritional status of children and adolescents can minimize clinical and metabolic changes, being determinant for the evaluation of the risk of disease progression and, consequently, treatment success.